Low-density lipoprotein receptor-related protein-1 (LRP1) in the glial lineage modulates neuronal excitability - Faissner, Andreas (Frontiers in Network Physiology, 2023)
The low-density lipoprotein related protein receptor 1 (LRP1), also known as CD91 or -Macroglobulin-receptor, is a transmembrane receptor that interacts with more than 40 known ligands. It plays an important biological role as receptor of morphogens, extracellular matrix molecules, cytokines, proteases, protease inhibitors and pathogens. In the CNS, it has primarily been studied as a receptor and clearance agent of pathogenic factors such as A-peptide and, lately, Tau protein that is relevant for tissue homeostasis and protection against neurodegenerative processes. Recently, it was found that LRP1 expresses the Lewis-X (Lex) carbohydrate motif and is expressed in the neural stem cell compartment. The removal of Lrp1 from the cortical radial glia compartment generates a strong phenotype with severe motor deficits, seizures and a reduced life span. The present review discusses approaches that have been taken to address the neurodevelopmental significance of LRP1 by creating novel, lineage-specific constitutive or conditional knockout mouse lines. Deficits in the stem cell compartment may be at the root of severe CNS pathologies.